Enhancing Tenth Graders' Reading Comprehension of Narrative Texts Using SQP2RS - Anita; Heru Setiawan (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
Reading is an essential skill that contributes significantly to the success of language learning; therefore, it should be prioritized. Reading skill needs comprehension to understand the context and get new information from the texts. To comprehend the texts, the readers need a strategy. This study aimed to find out whether or not there was any significant difference in students’ reading comprehension of narrative text between those who were taught by using SQP2RS and those who were not. This study used quasi quasi-experimental method to conduct the research. There were 72 students taken as samples using purposive sampling. In collecting the data, the result of the test was used as a pretest and posttest. To verify the hypothesis, the result of the Paired Sample T-Test found that the t-obtained was higher than 0.05. It indicated there was no significant improvement in students’ reading comprehension. Furthermore, the result of the independent sample t-test found that the t-obtained was lower than the t-table and the significance value of the Paired Sample T-Test was higher than 0.05. It indicated that there was no significant improvement in the tenth graders’ reading comprehension achievement. Meanwhile, the result of the Independent Sample T-Test showed that there was no significant difference in students’ reading comprehension between the experimental and control groups. Thus, it can be concluded that the SQP2RS strategy could not be an effective strategy to improve students’ reading comprehension of narrative text.